Extensive psoriasis induced by interferon alfa treatment for chronic hepatitis C. Issue 896 (1st June 2000) - Taylor, C; Burns, D A; Wiselka, M J
Abstract : A 47 year old man with chronic hepatitis C was treated with interferon alfa, 3 million units three times a week, and developed widespread plaque psoriasis within weeks of starting interferon therapy. There was no previous history of psoriasis. The psoriasis was characterised by extensive nail involvement and plaques at the interferon injection sites. The patient relapsed after a total of 12 months of interferon and was subsequently treated with interferon and tribavirin (ribavirin) with recurrence of the psoriasis.